PEMINJAMAN NAMA PERUSAHAAN OLEH DIREKSI KEPADA PIHAK KE TIGA DALAM PERSORAN TERBATAS - Sidrotul Akbar (Indonesia Private Law Review, 2020)
The actions of the Board of Directors in the form of lending the name of the company to other people who have the capacity to take legal actions on behalf of the company are basically actions that are contrary to Law of the Republic of Indonesia Number 40 of 2007 concerning Limited Liability Companies. If it is done, then it normatively can be understood that the Board of Directors has been negligent in carrying out its duties and responsibilities in running the company. This research was conducted on the basis of the problem regarding the concept of borrowing the company name as an ultra vires act and an analysis of the responsibilities of the Board of Directors for ultra vires actions. This research uses normative legal research methods.